Water deficit induces changes in H⁺-ATPase activity and its gene expres sion in Zea mays L. roots - Ovrutska, I.I.; Bluma, D.A. (Доповіді НАН України, 2016)
We investigated the functioning and the gene expression of H⁺-ATPase in the microsomal fraction enri ched with plasmalemma vesicles isolated from roots of two Zea mays cultivars: Dostatok (drought resistant) and Pereyaslivskiy (moderately tolerant to drought). Both cultivars grew during 21 days under the optimal water supply (soil moisture — 70 %, control) and during 10 days under the water deficit conditions (soil moisture — 30 %, experiment). An increase in the H⁺-ATPase hydrolytic activity in both cultivars under the water stress has been detected under drought. The enzyme hydrolytic activity is increased by twice in Dostatok and by1.3 times in Pereyaslivskiy. The H⁺-ATPase gene expression levels in both cultivars also increased under water deficit. It is shown that, in roots of both maize cultivars, the increase of four isoforms of H⁺-ATPase gene expression correlates with the increase of the hydrolytic enzyme activity under water stress conditions. However, these parameters are more sustainable in the drought-resistant cultivar Dosta tok, by allowing one value to use the hydrolytic activity of H⁺-ATPase as a biomarker of drought resistance for corn varieties. Досліджено функціонування Н⁺-АТФази в мікросомальній фракції, збагаченій фрагментами плазмалеми (ПМ) з коренів 21-добових рослин кукурудзи двох сортів: Достаток (посухостійкий) та Переяслівський (не посухостійкий), які зростали за умов достатнього водозабезпечення, при вологості субстрату 70 % та за умов водного дефіциту, протягом 10 діб, при вологості субстрату 30 %, а також експресію генів цього ензиму. Виявлено підвищення гідролітичної активності H⁺-АТФази в ПМ з коренів кукурудзи за умов посухи вдвічі в сорту Достаток і в 1,3 раза — в сорту Переяслівський. Встановлено, що рівень експресії генів у обох сортів за умов водного дефіциту був вищим, ніж за умов достатнього водозабезпечення, що корелює з даними гідролітичної активності ензиму, яка також була вищою в умовах дефіциту води. Причому ці показники мали більш сталий характер у посухостійкого сорту Достаток, що дає підставу використовувати значення гідролітичної активності H⁺- АТФази як біомаркер посухостійкості сортів кукурудзи. Проведены исследования функционирования H⁺-АТФазы в микросомальной фракции, обогащенной фрагментами плазмалеммы (ПМ) из корней 21-суточных растений кукурузы двух сортов: Достаток (засухоустойчивый) и Переясловский (не засухоустойчивый), которые росли в условиях достаточного водообеспечения, при влажности субстрата 70 % и в условиях водного дефицита, на протяжении 10 суток, при влажности субстрата 30 %, а также экспрессии генов этого энзима. Установлено повышение гидролитической активности H⁺-АТФазы в ПМ из корней кукурузы в условиях засухи в два раза у сорта Достаток и в 1,3 раза у сорта Переясловский. Показано, что уровень экспрессии генов у обоих сортов в условиях водного дефицита был более высоким, чем в условиях достаточного водообеспечения, что коррелирует с данными по определению гидролитической активности энзима, которая также была более высокой в условиях дефицита воды. Причём эти показатели имели более устойчивый характер у засухоустойчивого сорта Достаток, что позволяет использовать значения гидролитической активности H⁺-АТФазы в качестве биомаркера засухоустойчивости сортов кукурузы.